2014
DOI: 10.7243/2049-7962-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large b-cell lymphoma with hemophagocytic syndrome in an HIV+ patient treated with CCR5- bone marrow transplant

Abstract: Collective evidence points to a prominent role of stress in cancer growth and metastasis. Despite these results an etio-pathogenetic role has not been widely accepted. Reasons of controversies are the coexistence in stressed patients of high risk habits, the sample size, the heterogeneity and the retrospective origins of these studies. Experimental data and clinical observations argue about the possibility of an interaction between psychosocial events and tumours. However the number of involved variables and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
0
2
0
3
Order By: Relevance
“…According to him, life events, personality traits or depression cannot be proven with certainty that they play a role in cancer development [77]. Denario (et al), likewise, found a lack of links in her meta-analysis [78]. There are more articles that question the link between stress and neoplastic diseases, but there are also many publications that prove this link.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to him, life events, personality traits or depression cannot be proven with certainty that they play a role in cancer development [77]. Denario (et al), likewise, found a lack of links in her meta-analysis [78]. There are more articles that question the link between stress and neoplastic diseases, but there are also many publications that prove this link.…”
Section: Discussionmentioning
confidence: 99%
“…Stwierdzili, że żadne z tych badań nie wykazało istotnego związku między cechami osobowości a ryzykiem raka i że nie można z całą pewnością dowieść, że wydarzenia życiowe, cechy osobowości lub depresja odgrywają rolę w wystąpieniu raka [77] Brak związków wykazali również w swojej metaanalizie Denario i wsp. [78]. Artykułów, które kwestionują związek stresu z chorobami nowotworowymi, jest więcej, ale badań potwierdzających taki związek jest również wiele.…”
Section: Y S K U S J Aunclassified
“…Hasil penelitian terdapat korelasi antara stres, faktor psikologis dan kanker yang berfokus pada psikologi. (Russi, 2014). Penatalaksanaan kanker merupakan serangkaian intervensi, dimana didalamnya terdapat dukungan psikososial, pembedahan, radioterapi, kemoterapi yang bertujuan untuk mengurangi keluhan, menyembuhkan penyakit atau memperpanjang hidup dengan meningkatkan kualitas hidup pasien (Sweezey, 2014).…”
Section: Pendahuluanunclassified
“…Fiziksel hastalıklar, bireyin dengesini bozarak, kronik stres durumuna yol açabilmekte; başka bir deyişle sempatik sinir sistemine aşırı yük bindirmektedir. Yapılan çalışmalarda, diyabet (Anderson, 2001;Kılıçoğlu ve Gülcan, 2007), romatoit artrit (Onbaşıoğlu, 2006;Zautra, Smith ve Yocum, 2002), kanser (Denaro, Tomasello ve Russi, 2015), kalp-damar hastalıkları (Dickens, Mc Govan, Percival, Tomenson, Cotter ve ark., 2008), cilt hastalıkları (Kiec-Swierczynska, Dudek, Krecisz, Swierczynska-Machura, Dudek ve ark., 2006) gibi birçok hastalık grubunda stres ile bağlantılı psikiyatrik bozukluk oranı yüksek bulunmuştur. Tüberküloz hastalığının da bulaşıcı olması, yoğun ilaç kullanımını gerektirmesi ve tedavisinin uzun sürmesi, kuşkusuz stres faktörlerinin devreye girmesine neden olmaktadır.…”
unclassified